Vocal behaviour predicts mating success in giant pandas. Issue 10 (31st October 2018) - Charlton, Benjamin D.; Martin-Wintle, Meghan S.; Owen, Megan A.; Zhang, Hemin; Swaisgood, Ronald R.
Abstract : Surprisingly little is known about how mammal vocal signals are used to achieve behavioural synchrony in the lead up to copulation. The ability to signal short-term fluctuations in arousal levels and behavioural intention is likely to be particularly important for synchronizing mating behaviour in asocial species, which must overcome their natural avoidance and aggressive tendencies to mate. Here, we examined vocal behaviour during breeding encounters in captive giant pandas ( Ailuropoda melanoleuca ) to gain a greater understanding of how close-range vocal signalling mediates reproduction in this asocial, and conservation-dependent species. Our results revealed that the occurrence of different giant panda vocalizations and acoustic variation within these calls is predictive of successful encounters leading to copulation, as opposed to unsuccessful encounters that do not. In addition, key differences were detected between vocalizations produced during and just prior to copulation. These findings illustrate that vocal exchanges are crucial for achieving behavioural synchrony and signalling intention to mate in giant pandas, and could also provide a valuable tool for breeding programmes, helping conservation managers to assess the likelihood of breeding introductions leading to copulation or potentially injurious failure.